AN ERROR ANALYSIS IN WRITING THESIS ABSTRACT OF ENGLISH DEPARTMENT - Maskhurin Fajarina; Yuyun Bahtiar; Pipit Ertika Daristin (Universitas Islam Lamongan, 2022)
The goal of this study was to identify the different kinds of errors that were made by English Education Department students at KH. A. Wahab Hasbullah University of Jombang when they were writing their thesis abstracts. It also sought to understand why these errors could happen. This study concentrated on the thesis abstracts written by English education department undergrads. This study employed a descriptive qualitative methodology. Thirty undergraduate thesis abstract texts released in 2022 served as the research's source of data. Collection, identification, description, explanation, and evaluation of errors were the steps in the error analysis process. The method of data analysis was developed based on Corder's work, which was cited in (Nurdin & Sri Hartati, 2019). According to the results, undergrad students' mistakes included adding words, using the wrong terms, capitalizing, omitting words, spelling, punctuating, using the wrong tenses, and misusing word forms. These errors can be made in a variety of ways depending on their kind, and they can also result from carelessness, inadequate grasp of English grammar and vocabulary, and inter- and intra-lingual interference.